The Road Not Taken: A Comparison of the E.U. and U.S. Insider Trading Prohibitions - Franklin A. Gevurtz (Washington University Journal of Law & Policy, 2018)
This article, by Professor Franklin A. Gevurtz of the University of the Pacific’s McGeorge School of Law, explores the divergent approaches between the United States and the European Union with respect to the reach of insider trading laws. Finding that the current scope of E.U. law on insider trading is substantially similar to pre-1980 U.S. Law, Gevurtz compares the outcomes of similar high-profile U.S. and E.U. insider trading cases to illustrate just how different the outcomes are and where the U.S. would be had the Supreme Court kept a broad view on the law’s reach. Gevurtz then contrasts the jurisdictional reach of U.S. and E.U. laws and highlights issues involved in jurisdictional overlap. Finally, Gevurtz compares the normative discussions around insider trading prohibitions on the topics of market effects, fairness, and where to draw the line on who should be subject to the law’s reach.
Keywords: Chiarella; European Union; insider trading; Cady Roberts; Dirks; misappropriation; classical theory; traditional theory; fiduciary relationship; Market Abuse Directive; Article 2; intent; Einhorn; Cuban; English FSA; Newman; United States; Dell; Australia National Bank; Market Abuse Regulation; jurisdiction; Dodd-Frank; fairness; market effects